1990
DOI: 10.1056/nejm199011293232204
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Acute Exacerbations of Chronic Obstructive Lung Disease by Inspiratory Assistance with a Face Mask

Abstract: Inspiratory positive airway pressure delivered by a face mask can obviate the need for conventional mechanical ventilation in patients with acute exacerbations of chronic obstructive pulmonary disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
241
2
29

Year Published

1995
1995
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 614 publications
(299 citation statements)
references
References 24 publications
27
241
2
29
Order By: Relevance
“…Initial case series and uncontrolled cohort studies that suggested benefit in selected patients [1][2][3][4][5][6][7][8][9][10][11][12][13] led to many randomized controlled trials (RCTs). Both methods of ventilation have been used in the setting of acute respiratory failure to avoid endotracheal intubation in different patient populations and settings, with variable success.…”
mentioning
confidence: 99%
“…Initial case series and uncontrolled cohort studies that suggested benefit in selected patients [1][2][3][4][5][6][7][8][9][10][11][12][13] led to many randomized controlled trials (RCTs). Both methods of ventilation have been used in the setting of acute respiratory failure to avoid endotracheal intubation in different patient populations and settings, with variable success.…”
mentioning
confidence: 99%
“…In the study of BOTT et al [4], NIPSV was used for 6 days, as for patients in group I in the present study; however, respiratory acidosis was more significant for patients in the present study than in that of BOTT et al [4]. Some authors have previously proposed administering NIPSV discontinuously [1,4,5,20,23,24]. The sequential mode used on the present study is also a discontinuous mode, thus allowing comparison of the present results with those of other studies, with some specificity, i.e.…”
Section: Discussionmentioning
confidence: 49%
“…NIV via face mask or helmet has been the evidence-based treatment of choice in AECOPD patients with hypercapnia for more than 20 yrs [3]. NIV has been shown to improve gas exchange and outcome when compared with IMV.…”
Section: To the Editorsmentioning
confidence: 99%
“…Social deprivation scores were assigned to 1,896 lower super output areas (LSOAs) across Wales (average LSOA population 1,560) [3]. The LSOAs were ranked according to their social deprivation score and categorised into quintiles (I: least deprived; V: most deprived).…”
Section: To the Editorsmentioning
confidence: 99%
See 1 more Smart Citation